Comportamento do cimento supersulfatado (CSS) exposto ao ataque por sulfatos de origem externa - Trentin, Priscila Ongaratto (2020)
Portland cement (PC) is one of the most used construction materials in the world and draws attention due to the high amount of carbon dioxide emitted in its production. In this sense, supersulfated cement appears as an alternative to Portland cement, sinceit presents advantages such as the minimization of environmental impacts caused by the exploration of raw materials, low hydration heat and good durability in chemically aggressive environments, such as structures in contact with sewage and industrial effluents. Concrete is submittedto different forms of deterioration, both physical and chemical.A form of chemical and physical degradation of concrete is attack by sulfates, which causes expansion, cracking and reduction of strength. To minimize these problems, cements with additions are used, mainly with blast furnace slag, or sulfate-resistant Portland cement. The supersulfated cement (SSC) is constitutedof blast furnace slag (up until90%), calcium sulfate (10-20%) and a small amount of alkaline activator (up until5%), making it an excellent option to replace cement Portland, mainly to increase the resistance to attack by sodium sulfate. The objectiveof this study was to contribute to the assessment of resistance to attack by Na2SO4and MgSO4in supersulfated cements using the NIST Test methodology, that predictsthe use of paste specimens to accelerate the attack by sulfates.For this, using different SSCcompositions,with variation in the content and source of calcium sulfate,were performed tests ofmechanical resistance, water absorption, dimensional and mass variation, X-ray diffractometry (XRD), thermogravimetry (TG/DTG) and scanning electron microscopy (SEM). The results of dimensional and mass variation, for the attack by Na2SO4, show better behavior of the SSC in relation to the PC; in the attack by MgSO4, the samples of SSCproduced with 90% of slag and 10% of calcium sulfate suffered degradation and the samples with 80% slag and 20% calcium sulfate presentedexcessive expansion. The best results of mechanical resistance were presented by the PC,even in a situation of attack by sulfates. Microstructural analyzes (XRD, TG/DTG and SEM) presentedthe instability of hydrated products formed from supersulfated cements after 49 days of curing in Ca(OH)2solution. With this study it can be concluded that all SSCcompositions are resistant to attack by Na2SO4, having a better performance than PC. Despite this, the SSCsuffered degradation when exposed to the attack by MgSO4, presenting a behavior inferior to the PC. Thus, considering the tests of dimensional variation and mechanical resistance, determinants for the evaluation of resistance to attack by sulfates, the SSCproved to be suitable only for use in situations of attack by sodium sulfate.